The Impact of Sanitation on Increasing the Risk of Stunting in Children Under Five: A Meta-Analysis - Wahyu Aprilyaningsih; Bhisma Murti; Revi Gamma Hatta Novika; Sumardiyono Sumardiyono; Endang Sutisna Sulaeman (Indonesian Journal of Global Health Research, 2025)
Stunting among children remains a global public health issue, with as many as 149 milion children under the age of five affected worldwide. One of the contributing factors to stunting is poor sanitation. This research aims to estimate the extent to which poor sanitation contributes to the risk of stunting in children under five years old using a meta- analysis approach. study employed a systematic review and meta-analysis using the PICO framework (Population, Intervention, Controls/Comparisons, Outcome), defined as follows: Population: children under five years old; Intervention: poor sanitation; Comparison: good sanitation; Outcome: stunting. Articles were collected using PRISMA flow diagrams. A total of nine articles that met the quality standards were then included in the quantitative synthesis using meta-analysis. Articles were analysed using the Review Manager 5.3 application. The findings of this meta-analysis indicate a significant association between sanitation conditions and the risk of stunting in children under five. Children who live in environments with poor sanitation are 3.71 times more likely to experience stunting than those living in areas with good sanitation. Poor sanitation constitutes a major risk factor for stunting, which significantly impacts children's growth and development. Enhancing access to improved sanitation facilities and promoting good hygiene practices are priorities to prevent stunting, particularly in areas with high prevalence. These findings offer strong evidence to support the policymakers and other stakeholders in integrating sanitation- based interventions into public health programs to reduce the prevalance of stunting among children under five years of age.